The management of systemic lupus erythematosus - Rahman, Anisur (Henry Stewart Talks, 2017)
Clinical features, Current therapy, Pathogenesis and new therapies, Update talk: Belimumab (BLISS-LN), Update talk: Anifrolumab (TULIP), Update talk: Voclosporin (AURORA), Update talk: Obinutuzumab (NOBILITY and REGENCY), Update talk: CAR-T cell therapy, Update talk: Update of the management of systemic lupus erythematosus
Updated at 2025/11/30